Perlindungan Hukum Bagi Pihak Pembeli Akibat Cacat Tersembunyi Pada Transaksi E-Commerce Melalui Marketplace Shopee - Harum Tri Nugraheni; Suraji Suraji (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
This article aims to examine the form of legal protection for buyers due to the implementation of legal regulations in Indonesia regarding cases of hidden defects in e-commerce transactions. This research is normative legal research with primary, secondary and tertiary legal materials. This research uses a legislative approach which will then be analyzed using the syllogism method with a deductive mindset. The results of this research show that internal legal protection is created by the parties themselves, if the business actor commits a breach of contract in the form of selling goods that are not in accordance with the agreement, this can result in internal protection not being fulfilled. Meanwhile, the UUPK and PP PSTE are a form of external legal protection because they are regulations that have been made by authorized officials to provide protection to weak parties from injustice.